1585 Unilateral Versus Bilateral Surgery for Inguinal Hernia in Premature Boys: A Multicenter French Study On 966 Cases. (October 2012) - Maillet, O; Garnier, S; Podevin, G; Leclair, MD; Arnaud, A; Fremond, B; Linard, C; Compagnon, R; Fourcade, L; Jaby, O; Ponet, M; Ghoneimi, A El; et al.
Abstract : Background and Aim: Bilateral surgery was formerly advocated in premature boys with unilateral inguinal hernia to avoid a metachronous contralateral hernia and the risks of recurrent anesthesia. But the recent progress in pediatric anesthesia and the demonstrated morbidity of herniotomy during the neonatal period on fertility now question this attitude. We aimed to compare the morbidity of preventive bilateral vs elective unilateral herniotomy in premature boys with unilateral hernia and to evaluate the incidence of contralateral metachronous hernia. Methods: Retrospective multicenter analysis of 966 premature boys presenting with unilateral inguinal hernia. 558 infants benefited from unilateral herniotomy and 408 from bilateral herniotomy with a median follow up of 20 months. Results: The rate of contralateral metachronous hernia after unilateral surgery was 11% (10% on right vs 13% on left). Morbidity on the contralateral side was higher in case of preventive bilateral surgery than in metachronous hernia (2% vs 0.2% p=0.003), especially for testicular hypotrophy (0.70% vs 0.18 %, p= 0.3) and secondary cryptorchidism (1% vs 0%, p=0.03) Comparison between the type anesthesias (general anesthesia versus central block) did not show significant differences depending on the type of care (unilateral or bilateral, planned or emergency). Conclusion: Systematic bilateral herniotomy is unnecessary in almost 90% of patients and has a higher morbidity than secondary surgery for metachronous hernia. These results, along with the risk of deferential damage and hypofertility reported in later adulthood, justify treating only the symptomatic side in premature boys.